Indonesia's Mineral Export Prohibition and Legality of Export Duties Under the GATT Rules - Bani Adam; Haniff Ahamat (Faculty of Law, Sriwijaya University, Indonesia, 2022)
The development of electric vehicles has been becoming a global trend to tackle worsening air pollution. The rich mineral country desires to reduce greenhouse gas (GHG) through transportation transformation by building a domestic-based battery vehicle industry. The policy resulted in importing export restrictions on nickel ore and bauxite by the Indonesian government. However, the measures are inconsistent with Article XI.1 of the GATT rules, which forbid imposing restrictions on the global market. There are cases in WTO DSB deciding that export restrictions infringe the provision, such as in China – Raw Materials (DS394) and China – Rare Earth (DS431) cases. In such cases, adjudicators also do not justify the imposition of export duties for the members. Meanwhile, Article XI.1 does not prohibit the imposition of export duties as another option to impose export restraints. The Indonesian authority could apply the measures. This Article analyses Indonesia's justification for imposing export control through the GATT rules. The research is conducted based on a normative juridical approach in which the sources come from the rules of GATT and its DSB decision to analyse the extent to which the measures are allowed to take into force for the member regarding the GATT provisions. The Article finds that Indonesia may be justified in the imposition of export duties to control the export of both raw materials. Article XI.1 of GATT justifies the original and accepted members to impose the duties measures as there are unclear provisions on export prohibition, which means Indonesia could enforce the charge of duties implicitly.